Thomas Browne and the Silent Text - Wolfe, Jessica (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
Throughout his writings, the physician and essayist Thomas Browne (1605–82) grapples with the problem of how and whether to interpret the silence of texts. His innovative solutions to the problem of “negative authority,” the term used in early modern theological debates over the significance, or lack thereof, vested in things omitted by the scriptures, challenge more conventional reformed defenses of scriptural perspicuity and also reveal how these hermeneutic puzzles in turn shape Browne’s understanding of the relationship between theology and natural philosophy and between rhetoric and logic. This article analyzes Browne’s idiosyncratic treatment of textual silence within its historical moment and also considers the interpretive challenges posed by omissions in Browne’s own writings, focusing in particular on his Pseudodoxia Epidemica.